Jihaaz al-'Ashobiy wa Dauruhuu Fii Dzuhuur Lughat al-Insaan - Mohammad Zainal Hamdy (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2021)
This study aims to reveal the nervous system in the human speech process with the point of view form a psycholinguistic analysis. This study uses a qualitative approach to the type of literature study. The results showed that understanding language, like producing it, is such an automatic importance that it may seem an easy-to-forget process. The sounds or letters fall on our ears or our eyes quickly, creating the words that make up simple and complex phrases and sentences. So understanding is little more than recognizing a succession of linguistic symbols with very rapid impact. But what appears on the surface to be